Development of novel strategies based on Lewis acid and transition metal mediated stereoselective c-glycosylation - Zeng, Jing (2013)
The significance of C-glycosides has stimulated a wide interest in the development of C-glycosylation methods. Among them, Lewis acid and transition metal mediated direct attachment of carbon nucleophiles to sugar anomeric carbon center to produce 2,3-unsaturated glycosides and saturated, fully oxygenated glycosides are probably the most widely used methods. This thesis work focuses on the development of new methodologies in Lewis acid and transition metal mediated stereoselective C-glycosylation and application of these methodologies to natural product synthesis.